A Constructivist Flipped Learning Approach to Enhance EFL Majors' Writing Performance at Al Azhar University – Gaza - Fidaa Soboh; Asmaa Gheith (Port Said Journal of Educational Research)
The current study aimed to enhance the EFL majors' writing performance by adopting a constructivist flipped learning approach. The researchers adopted one group design. Participants were thirty-one EFL majors (n=31), enrolled in the study program, who had 10 sessions; approximately two days per week, two hours per session. To identify and enhance the participants' writing performance, the researchers designed a pre/post-test and a rubric. The researchers then created a program based on the constructivist flipped learning approach to enhance the learners' writing performance. The pre/post-test results of the participants were analyzed statistically by using Pearson's correlation coefficients and Cronbach's Alpha Coefficient to compare the mean score, standard deviation, and effect size. In addition, a qualitative analysis of the participants' progress was conducted and analyzed. Both quantitative and qualitative interpreted results revealed varied positive effects of using the constructivist flipped learning approach in enhancing EFL majors' writing performance.